ANÁLISE EXPERIMENTAL DA EVOLUÇÃO DA CARBONATAÇÃO EM ARGAMASSAS DE CAL AÉREA - Almeida, Emerson (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
For centuries, aerial lime has been frequently used as binder for preparing mortar in masonry buildings. Knowledge about the material behavior of aerial lime mortars is however still reduced, and contributions are necessary for better understanding its physical and mechanical properties, in this work, an experimental program is done to investigate the evolution of carbonation process. It starts with the definition of mortar composition, a typical composition is adopted. Specimens with reduced thickness were stored in three different chambers. The first chamber presents ordinary environmental conditions, while the other two environments present elevated humidity or CO2 concentration. Thermogravimetric analysis was done at five ages, and the results indicate a progressive increase of the carbonation, however, an incomplete carbonation process was observed, therefore a normalization was adopted. The data show a faster carbonation process for the specimen stored in the chamber with elevated CO2 and a reduced evolution of mortar stored in the humid chamber at the first ages.